2022
DOI: 10.1155/2022/1749616
|View full text |Cite|
|
Sign up to set email alerts
|

KANO Model-Enabled Performance Evaluation of Urban Public Sports Services

Abstract: Starting from the goal of overall equalization of basic public services by 2035 as proposed in the report of the 19th Party Congress, firstly the research history of the equalization of public sports services in China is analyzed in stages, and a solid theoretical foundation is laid for the construction of the evaluation index system. Secondly, the performance evaluation system of urban public sports services, which is based on KANO model, is constructed by combining the current development status of public sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Kano model was proposed by a Japanese professor named Kano in 1984 ( 17 ). In accordance with the relationship between the subjective feelings of customers and the objective performance of products, the Kano model divided the service attributes into must-be qualities (M), one-dimensional qualities (O), attractive qualities (A), indifferent qualities (I) and reverse qualities (R) ( 18 ), as shown in Figure 1 . Must-be qualities are features that, if not provided, may make users dissatisfied, however, when they are provided, they will not improve users' satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The Kano model was proposed by a Japanese professor named Kano in 1984 ( 17 ). In accordance with the relationship between the subjective feelings of customers and the objective performance of products, the Kano model divided the service attributes into must-be qualities (M), one-dimensional qualities (O), attractive qualities (A), indifferent qualities (I) and reverse qualities (R) ( 18 ), as shown in Figure 1 . Must-be qualities are features that, if not provided, may make users dissatisfied, however, when they are provided, they will not improve users' satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%